Statistics in Biosciences - Statistics in Biosciences (Springer Nature, 2026)
Statistics in Biosciences (SIBS) is published three times a year in print and electronic form. It aims at development and application of statistical methods and their interface with other quantitative methods, such as computational and mathematical methods, in biological and life science, health science, and biopharmaceutical and biotechnological science.
FI 0.27
Q4
Keywords: Mathematics & Statistics; Matemáticas; Biociencias; Acuerdos transformativos; Transformative agreements; Métodos estadísticos; Métodos computacionales; Ciencias biológicas y de la vida